DUKUNGAN KELUARGA TERHADAP PEMBERIAN ASI EKSKLUSIF PADA BAYI DI KOTA JAMBI - Nurlinawati - -; Junaiti Sahar; Henny Permatasari (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2016)
Abstract   Exclusive breast feeding program coverage in Indonesia and Jambi is still relatively low, although Indonesian government had launched thisexclusive breast feeding program in 2010 that at least 80%baby should be covered in the program. The purpose of this study was to examine the correlation between family support on exclusive breast feeding and the coverage of the program on baby in Jambi. This is descriptive correlation study used cross sectional in recruiting 70 mothers who have 0-6 months oldbaby. The sample was recruited using cluster sampling. The result shows that there is significant correlation between information, instrumental, emotional, and acknowledgement support on exclusive breast feeding and the most dominant on family support was instrumental support. It is recommended that nurses’ role in the community is needed to motivate family in giving instrumental support in exclusivebreast feeding program for baby.   Keywords: exclusive breast feeding, family support, instrumental support